2022
DOI: 10.3389/fpsyg.2022.847274
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction and Its Associated Factors Among African High School and University Students: Systematic Review and Meta-Analysis

Abstract: IntroductionInternet addiction is characterized by excessive and uncontrolled use of the internet affecting everyday life. Adolescents are the primary risk group for internet addiction. Data on internet addiction is lacking in Africa. Thus, this review aimed to determine the pooled prevalence of internet addiction and its associated factors among high school and university students in Africa.MethodsA comprehensive literature search was conducted using electronic databases (PubMed/MEDLINE, Web of science, Hinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 87 publications
1
24
0
1
Order By: Relevance
“…The identified discrepancy between the analyzed countries requires further investigation. The results can be compared to those of Zewde et al (40) who found in their study that students from urban areas are more likely to be addicted to the internet. It is generally known that urban areas are more internet accessible and urban individuals make greater use of the internet, which may explain the higher rates of addictive behavior in urban areas (80)(81)(82).…”
Section: Residencementioning
confidence: 90%
See 4 more Smart Citations
“…The identified discrepancy between the analyzed countries requires further investigation. The results can be compared to those of Zewde et al (40) who found in their study that students from urban areas are more likely to be addicted to the internet. It is generally known that urban areas are more internet accessible and urban individuals make greater use of the internet, which may explain the higher rates of addictive behavior in urban areas (80)(81)(82).…”
Section: Residencementioning
confidence: 90%
“…In both countries, male students were more likely to suffer from internet addiction than female students. Other studies also revealed a higher risk of problematic internet use or internet addiction in male students compared to female students (18,38,(40)(41)(42)(43). The predominance of males in this type of problematic behavior is evident (77).…”
Section: Gendermentioning
confidence: 93%
See 3 more Smart Citations